Effects on Growth and Yield of Eggplant (Solanum Melongema l.) Under Placement of Drip Laterals and Using Municipal Wastewater†. (22nd April 2016) - Tripathi, Vinod Kumar; Rajput, T.B.S.; Patel, Neelam; Kumar, Pradeep
Abstract: This study was conducted to utilize municipal wastewater through surface and subsurface (15 and 30 cm) drip systems. Wastewater was treated though media type, disk type and combined media and disk type filters. The field experiment was conducted for two years with wastewater and groundwater. Root length density (RLD), leaf area index (LAI), and fruit yield with dry matter was recorded. LAI was lower under subsurface drip during the initial 55 days after transplantation, but in later stages it was significantly higher in comparison to surface drip. Highest RLD of 3.6 cm cm –3 was recorded under subsurface drip at 30 cm depth. RLD and LAI were related with a correlation coefficient value of 0.69. Highest dry matter content (8.75%) was recorded under surface drip but highest fruit yield was recorded under subsurface placement of drip at 15 cm depth. Subsurface drip at 15 and 30 cm depths resulted in 12.4 and 8.5% higher yields respectively, in comparison with surface drip. Utilization of wastewater through a drip irrigation system has given 6.2% increase in eggplant fruit yield in comparison to groundwater irrigation, with savings of 47, 18 and 40% of N, P2 O5 and K2 O nutrients respectively. The findings of the present study elucidate the potentials and constraints of wastewater utilization through a subsurface drip system. Copyright © 2016 John Wiley & Sons, Ltd.